Folic Acid Preconditioning Alleviated Radiation-Induced Ovarian Dysfunction in Female Mice - Zhang, Qianyu; Wei, Zhifu; Weng, Huinan; Chen, Ye; Zhang, Jie; Mei, Shiwei; Wei, Jiahui; Zhu, Xiulan; Nong, Yingqi; Ruan, Jianxing; Liu, Wenjuan; Zhou, Ruiqiong; et al. (Frontiers in Nutrition, 2022)
Radiological therapy/examination is the primary source of artificial radiation exposure in humans. While its application has contributed to major advances in disease diagnosis and treatment, ionizing radiation exposure is associated with ovarian damage. The use of natural products, either alone or as an adjunct, has become increasingly common for reducing the side effects of radiological therapy during disease treatment. Herein, we explored the protective effect of folic acid (FA), a widely used B vitamin, against radiation-induced ovarian injury and its mechanism of action. Female mice with normal ovarian function were randomly divided into control, FA, radiation, and radiation + FA groups. The intervention strategy included daily intragastric administration of FA (5 mg/kg) for 3 weeks prior to radiation exposure. Mice in the radiation and radiation + FA groups received a single dose of 5 Gy X-ray irradiation. Changes in the estrous cycle were then recorded, and ovarian tissues were collected. Pathophysiological changes as well as reproductive and endocrine-related indexes were determined via H&E staining, immunohistochemistry, western blot, and ELISA. The reproductive performance and emotional symptoms of animals were also monitored. Our results indicated that FA intervention effectively alleviated ovarian damage, leading to more regular estrous cycles, lesser impairment of follicular morphology and endocrine status, as well as greater germ cell preservation. Reduced levels of oxidative stress, inflammation, and enhanced DNA repair were associated these changes. FA pre-administration improved the reproductive performance, leading to higher pregnancy rates and greater litter sizes. Further, the anxiety levels of animals were significantly reduced. Our results indicate that FA pre-administration significantly alleviates radiation-induced ovarian damage in rodents, highlighting its potential as a protective strategy against radiation exposure in the female population.